The LiLa Lemma Bank: A Knowledge Base of Latin Canonical Forms. - Mambrini, Francesco; Passarotti, Marco Carlo (Journal of Open Humanities Data, 2023)
The dataset contains a list of 215,102 Latin dictionary forms (known as canonical forms or lemmas). The dataset is a set of 1,699,687 Resource Description Framework (RDF) triples that describe, using a series of Web Ontology Language (OWL) ontologies for Linguistic Linked Data, the morphological properties of these forms. The dataset is used to link together a series of corpora and dictionaries in the interoperable network of language resources published by the LiLa: Linking Latin project.